CT‐guided percutaneous transthoracic needle biopsy (PTNB): A thoracic surgeon's learning curve and experience summary. Issue 7 (17th January 2023) - Hong, Tao; Ji, Guijuan; Sun, Teng; Gui, Xin; Ma, Tianyue; Zhang, Hao
Abstract: Background: Few studies have investigated the learning process of percutaneous transthoracic needle biopsy (PTNB). Here, we aimed to evaluate the number of cases required to achieve proficiency by plotting the learning curve of PTNB. Methods: Data were collected from 94 consecutive patients who underwent computed tomography–guided PTNB by a thoracic surgeon at the Affiliated Hospital of Xuzhou Medical University between May 2021 and February 2022. The data collected included patient information, relevant examination results, intraoperative parameters, postoperative complications, and diagnostic results. Results: The inflection points of the cumulative sum curve were around cases 13 and 24, according to which three phases were identified, including phase I, phase II, and phase III. A significant downtrend was observed regarding operative time (phase I, 26.53 ± 9.13 min vs. phase III, 18.42 ± 4.29 min, p  < 0.05), rate of false‐negative (phase I, 15.4% vs. phase III, 5.7%; p  < 0.05), rate of pneumothorax (phase I, 30.8% vs. phase III, 12.9%; p  < 0.05), and rate of hemoptysis (phase I, 15.4% vs. phase III, 2.9%; p  < 0.05). Conclusions: Thirteen cases were accumulated to lay the technical foundation, and 24 cases were required to achieve proficiency. In this study we summarize our own experience and provide specific guidance for young doctors with no experience in biopsy. Abstract : Learning curve of PTNB.